The Coupled Thermal Response Analysis of Green Roofs Based on the Discrete Element Method - Chang Liu; Xiaoyong Zhang; Mingjie Jiang; Shengnan Zhu; Zhuan Wang; Jianxu Long (Buildings)
As an effective energy-saving measure, green roofs significantly improve the thermal environment of buildings by covering the roof with vegetation and soil. This paper compares the thermal transfer performance of concrete roofs and green roofs under different temperature conditions. First, a uniaxial compression discrete element method (DEM) was used to calibrate the mesoscopic parameters of concrete, ensuring an accurate representation of concrete properties. The results indicate that green roofs have significant insulation effects under high-temperature conditions in summer. After being exposed to high temperatures for 5 h, the temperature of the green roof was 23.4 degrees Celsius lower than that of the ordinary concrete roof. In addition, different initial temperatures of the model also have a certain impact on heat transfer. The higher the initial temperature, the slower the temperature increase under high-temperature conditions. In winter, the green roof significantly delays the cooling at the top of the building, demonstrating excellent thermal insulation performance. The maximum temperature difference compared with the concrete roof is 8 °C. Finally, there is an exponential relationship between the thermal resistivity of the green roof and the temperature. In conclusion, green roofs have significant energy-saving and environmental protection value.